Phylogenomics of Scorpions Reveal Contemporaneous Diversification of Scorpion Mammalian Predators and Mammal-Active Sodium Channel Toxins. (28th March 2022) - Santibáñez-López, Carlos E; Aharon, Shlomi; Ballesteros, Jesús A; Gainett, Guilherme; Baker, Caitlin M; González-Santillán, Edmundo; Harvey, Mark S; Hassan, Mohamed K; Abu Almaaty, Ali Hussein; Aldeyarbi, Shorouk Mohamed; Monod, Lionel; Ojanguren-Affilastro, Andrés; et al.
Abstract: Scorpions constitute a charismatic lineage of arthropods and comprise more than 2500 described species. Found throughout various tropical and temperate habitats, these predatory arachnids have a long evolutionary history, with a fossil record that began in the Silurian. While all scorpions are venomous, the asymmetrically diverse family Buthidae harbors nearly half the diversity of extant scorpions, and all but one of the 58 species that are medically significant to humans. However, the lack of a densely sampled scorpion phylogeny has hindered broader inferences of the diversification dynamics of scorpion toxins. To redress this gap, we assembled a phylogenomic data set of 100 scorpion venom gland transcriptomes and genomes, emphasizing the sampling of highly toxic buthid genera. To infer divergence times of venom gene families, we applied a phylogenomic node dating approach for the species tree in tandem with phylostratigraphic bracketing to estimate the minimum ages of mammal-specific toxins. Our analyses establish a robustly supported phylogeny of scorpions, particularly with regard to relationships between medically significant taxa. Analysis of venom gene families shows that mammal-active sodium channel toxins (NaTx) have independently evolved in five lineages within Buthidae. Temporal windows of mammal-targeting toxin origins are correlated with the basal diversification of major scorpion mammal predators such as shrews, bats, and rodents. These results suggest an evolutionary model of relatively recent diversification of buthid NaTx homologs in response to the diversification of scorpion predators. [Adaptation; arachnids; phylogenomic dating; phylostratigraphy; venom.]